Trends in individual income growth: Measurement methods and British evidence - Stephen P. Jenkins; Philippe Van Kerm (Institute for the Study of Labor (IZA), 2011)
Assessments of whose income growth is the greatest and whose is the smallest are typically based on comparisons of income changes for income groups (e.g. rich versus poor) or income values (e.g. quantiles). However, income group and quantile composition changes over time because of income mobility. To summarize patterns of income growth while also tracking the fortunes of the same individuals, a longitudinal perspective is required. For this case, we develop dominance conditions and summary indices for comparisons of distributions of individual income growth, together with associated methods of estimation and inference. Using these methods and data from the British Household Panel Survey, we study individual income growth for periods between 1991 and 2005. We show that income growth was significantly more pro-poor in the early years of the Labour government than in earlier Conservative years.
urn:nbn:de:101:1-201104113833
Keywords: D31; D63; I32; 330; individual income growth; pro-poor growth; progressive income growth; income mobility; mobility profile; British Household Panel Survey; Einkommensverteilung; Soziale Mobilität; Armut; Schätzung; Großbritannien